2011
DOI: 10.1504/ijbis.2011.041787
|View full text |Cite
|
Sign up to set email alerts
|

Strategic sustainability and operational efficiency dilemma of data centres

Abstract: The core discussion is based on three large service companies that were analysed from a case study-perspective in terms of green energy options for its data centres, especially maintenance efforts to increase efficiency of their data centres while maintaining required levels of reliability and cooling. The components of operational effectiveness and strategy broke down into many parts. Following strategic initiatives and balancing the operational effectiveness of the firms studied, it was suggested that these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…We provide approaches to strategic sustainability in Figure 5. Nowadays, companies' and projects' management is faced with the necessity to strike a balance between operational effectiveness and strategic thinking on the sustainability issue [88]; in our opinion, this is the cornerstone for the achievement of strategic sustainability.…”
Section: Strategic Sustainabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…We provide approaches to strategic sustainability in Figure 5. Nowadays, companies' and projects' management is faced with the necessity to strike a balance between operational effectiveness and strategic thinking on the sustainability issue [88]; in our opinion, this is the cornerstone for the achievement of strategic sustainability.…”
Section: Strategic Sustainabilitymentioning
confidence: 99%
“…Several studies attempted to assess sustainability of resource exploration in the Arctic in terms of environmental aspects, such as the rational use of mineral resources, ensuring a high level of energy and resource efficiency, reducing the environmental impact, and preserving fragile ecosystems [93]. Gassiy et al concluded that the SD of the Arctic systems is determined by a balance between the interests of key Nowadays, companies' and projects' management is faced with the necessity to strike a balance between operational effectiveness and strategic thinking on the sustainability issue [88]; in our opinion, this is the cornerstone for the achievement of strategic sustainability.…”
Section: Efficiency/sustainability Assessment Of Arctic Oil and Gas P...mentioning
confidence: 99%